Spiritual Spiritual Therapy (Dhikr) can Decrease Blood Sugar Levels in Diabetes Mellitus Patients in the Intensive Care Unit (ICU): A Study Literature - Henggar Awang Anjastya; Wachidah Yuniartika (LPPM STIKes Karya Kesehatan, 2022)
Diabetes Mellitus is a metabolic disorder of the distribution of glucose that cannot produce and utilize the hormone insulin optimally so that it can cause an increase in blood glucose levels that exceed normal limits. Dhikr therapy can provide a relaxing effect and calm the soul which can affect the production of the hormone cortisol so that it can reduce blood glucose levels. The purpose of the study was to determine spiritual dhikr therapy to reduce blood sugar levels in diabetes mellitus patients in the Intensive Care Unit Room. This research is a literature review research by analyzing and comparing several articles through searches on journal sites such as Google Scholar and PubMed using the keywords Spiritual therapy of dhikr, blood sugar, diabetes mellitus and in 2016-2021. The result of this literature review is that spiritual remembrance therapy is efficient to reduce blood sugar levels in diabetes mellitus patients who are treated in the Intensive Care Unit. The conclusion of this study is that Spiritual dhikr therapy is a form of intervention that can be carried out by families or nurses as stimulation to patients who can help reduce blood sugar levels in patients with diabetes mellitus. Based on the results, it can be found that the spiritual dhikr therapy intervention can effectively reduce blood sugar levels in patients and it is recommended for type 2 DM patients to use spiritual therapies such as dhikr to lower blood sugar levels.